Peningkatan Pengetahuan Masyarakat tentang Pencegahan Covid-19 di Desa Bambu Kabupaten Mamuju - Akbar Nur; I Kadek Dwi Swarjana; Marlin Eppang; Nini Sahrianti S; Wita Oileri Tikirik (Jurnal Abdimas Kesehatan (JAK), 2022)
Corona Virus or known as COVID-1 9 has now spread to various countries in the world. The World Health Organization (WHO) has declared COVID-19 a global emergency. The government has made efforts to prevent the spread of Covid-19, namely by socializing 3M and 3T. The term 3M is a health protocol that every individual needs to do to avoid contracting Covid-19, namely wearing masks, washing hands, and keeping a distance. On the other hand, to identify residents who have been exposed to Covid-19, the government has termed 3T efforts, namely testing (examination), tracing (contact tracing), and treatment. The main steps that the community can take to reduce and anticipate the spread of Covid-19 are the use of masks, covering the mouth and nose when sneezing or coughing, washing hands with soap or disinfection. The purpose of this community service activity is to increase public knowledge about the prevention and implementation of health protocols during the COVID-19 pandemic. The form of activities in community service carried out by STIKES lecturer Andini Persada Mamuju by conducting health education, distributing masks, and distributing hand sanitizers. The lack of public awareness and knowledge regarding Covid-19 can be overcome by providing information in the form of health education about the importance of implementing health protocols. . This step is something that must always be applied by the whole community, especially the people of the Bamboo Village, Mamuju Regency. Information and education must continue to be provided to the public, as well as carry out supervision so that people want to implement healthy lifestyle behaviors to prevent the spread of Covid-19. Socialization activities in the form of health education, distribution of masks, hand sanitizers are one effective way to educate the public.